1992
DOI: 10.1002/ajim.4700210603
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of occupational exposure to cadmium in the Netherlands, 1980–1989

Abstract: One thousand five hundred fifty urine samples and 1,295 blood samples, collected from 919 workers, were analyzed for cadmium (Cd). The workers were employed at 16 different types of workplaces. In about 7.5% of the samples, the concentration of Cd exceeded the biological limit values proposed by the Dutch Expert Committee for Occupational Standards. Levels higher than these values were measured in both urine samples and blood samples of workers involved in electrochemical plating, in production of Cd-stabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…The major sources of cadmium to the environment include battery industry, nickel-cadmium battery manufacturing[3] plastic industries, smelting and refining of metals (e.g. Zinc refining/Cadmium smelting and production[4] lead smelting and refining, iron and steel production, cadmium-containing pigment production[5] dry color formulating, cadmium-based stabilizer production, coal-fired electrical utilities and garbage incineration[6] fertilizers[79] metal plating with cadmium-containing materials[5] production of cadmium alloys. Cigarettes are also a significant source of cadmium exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The major sources of cadmium to the environment include battery industry, nickel-cadmium battery manufacturing[3] plastic industries, smelting and refining of metals (e.g. Zinc refining/Cadmium smelting and production[4] lead smelting and refining, iron and steel production, cadmium-containing pigment production[5] dry color formulating, cadmium-based stabilizer production, coal-fired electrical utilities and garbage incineration[6] fertilizers[79] metal plating with cadmium-containing materials[5] production of cadmium alloys. Cigarettes are also a significant source of cadmium exposure.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Most studies on cadmium toxicity, therefore, centres on the detection of early signs of kidney dysfunction which results from oxidation. [5] In other words, Cd causes its injurious effects by generation of reactive oxygen species (ROS). [5]…”
Section: Introductionmentioning
confidence: 99%
“…[5] In other words, Cd causes its injurious effects by generation of reactive oxygen species (ROS). [5]…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of Cd compounds on the production of lipid peroxidation, decreased glutathione content and glutathione peroxidase, were noticed in the ventral prostrate lobe, liver cells and testicular tissues of animals (Alvarez et al, 2004;Ikediobi et al, 2004;Sengupta et al, 2004). Studies relating to occupational exposure to Cd during the Cdplating process have reported nasal toxicity and renal tubular dysfunction (Zwennis and Fransen, 1992;Rydzewski et al, 1998;Sunderman FW Jr, 2001). Since no reports are available regarding occupational exposure to Cd and the effects on oxidative stress, the present study was undertaken to investigate the generation of free radicals involved in plasma lipid peroxidation and the potential effects on erythrocyte superoxide dismutase and glutathione peroxidase in workers exposed to Cd during the Cd-plating process.…”
Section: Introductionmentioning
confidence: 99%